2023
DOI: 10.1007/s00264-023-05699-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of muscle necrosis in patients with acute compartment syndrome

Abstract: Purpose The predictors of muscle necrosis after acute compartment syndrome (ACS) remain debated. This study aimed to investigate the predictors for muscle necrosis in ACS patients. Methods We collected data on ACS patients following fractures from January 2010 to November 2022. Patients were divided into the muscle necrosis group (MG) and the non-muscle necrosis group (NG). The demographics, comorbidities, and admission laboratory indicators were computed by univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Acute compartment syndrome (ACS) is a severe orthopedic emergency that affects 1-30.4% of patients with lower extremity fractures, based on previous reports (1)(2)(3). It is characterized by rapidly increased pressure within a closed compartment after trauma, causing bleeding, tissue edema, and reduced limb perfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute compartment syndrome (ACS) is a severe orthopedic emergency that affects 1-30.4% of patients with lower extremity fractures, based on previous reports (1)(2)(3). It is characterized by rapidly increased pressure within a closed compartment after trauma, causing bleeding, tissue edema, and reduced limb perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…A delay in diagnosis or treatment can result in unimaginable outcomes, such as sensory deficits, paralysis, infection, or muscle necrosis (4)(5)(6). Our latest studies have reported that neutrophils (NEU) and creatine kinase myocardial bands (CKMB) may be biomarkers of ACS (2,7). However, there was a limited number of complete blood counts and derived inflammatory indicators.…”
Section: Introductionmentioning
confidence: 99%